Case study analysis of Defense Experimentation to support Network Enabled Capability development. (April 2013) - Arnott, Shane D; Lindsay, Peter A
Defense Experimentation (DE) using modeling and simulation (M&S) is increasingly being adopted as a means to better understand complex defense capability problems. This is being given added impetus by the amplified focus on Network Enabled Capability (NEC) and the rising use of advanced information and communications technology within military operations. This paper presents analysis of observed data trends from a broad range of DE experiments performed within capability development programs for the United Kingdom and Australian Governments over the period of 2001–2010. A range of variables were tracked concerning the experiment's nature, the DE method employed, M&S technology utilized and human resources used across the experiment life cycle. Time and effort results are presented here, broken down by DE method and life-cycle phase. The paper also analyses where reuse took place in the experiment life cycle, and how time and effort were affected by the number of problem-owner and provider stakeholders involved. The insights yielded are expected to help DE planners improve estimation and scheduling of human resources. In turn, this is intended to facilitate delivery of more effective NEC concept development and experimentation.